Shreds of war : fates from the Donbas frontline, 2014-2019 - Eperjesi, Ildikó; Kachura, Oleksandr (Ukrainian voices (Stuttgart, Germany), 2022)
"In Eastern Ukraine, unfathomable human dramas have unfolded since 2014. Thousands died in the fighting. The homes of tens of thousands were destroyed. Many were captured and tortured, millions ousted from their homes. The lives of many were broken. Volunteers started to collect food, clothes and even weapons for the frontline. Charity organizations transferred donations to the Donets' Basin (Donbas). Priests became chaplains for soldiers. Journalists and photographers flooded into the war-zone and sometimes became involved in the events. A Hungarian and Ukrainian journalist, Eperjesi and Kachura had the opportunity to meet and talk to many of these characters. The book provides a tableau of the emblematic figures of the war in the Donbas. It not only presents tragedies, but also human moments and noble deeds. The two journalists show how the lives of ordinary people have changed as a result of the horrors of war. They also spoke to pro-Russian militiamen and even with a Russian military officer captured in Ukraine. Shreds of War is one of the few authentic books with on-the-spot coverage, interviews, and dramatic photos documenting the war in Eastern Ukraine."--